Education Financing to Improve Quality of Education in Indonesia - Siti Chaerijah Aurijah; Martinus Tukiran (Cita Konsultindo Research Center, 2025)
Education aims to educate the life of the nation. One of the factors that can improve the quality of education is education financing, this is because education financing provides convenience in education management. This study uses the systematic literature review method with the PRISMA model. By collecting and analyzing as many as 10 journal articles published in 2020-2024. The results of the study show that education financing can improve the quality of education and the cost is closely related to improving the quality of education. In conclusion, the cost of education is closely related to improving the quality of education in Indonesia.